The Art of Making Smart Big Moves - STREBEL, Paul (Institutional Knowledge at Singapore Management University, 2006)
For many companies, incremental growth is not sufficient. The changing business landscape is forcing corporate leaders to learn how to reposition their businesses more fundamentally.